Najin Gradnik - Hladnik, Miran (Jezik in slovstvo, 2017)
The paper reports on the editorial dilemmas and experiences of Miran Hladnik and Tone Pretnar in preparing five books of collected poetic works (1984-2008) by Alojz Gradnik (1882-1967) for critical edition.
Keywords: Gradnik, Alojz, 1882-1967; Zbrano delo; Pretnar, Tone, 1945-1992; Hladnik, Miran, 1954-; Slovene literature; slovenska književnost; slovenski pisatelji; zbrana dela; kritične izdaje; uredništko delo